Media Pembelajaran Matematika Berbasis Edutainment dengan Pendekatan Metaphorical Thinking dengan Swish Max - Sukma, Agustien Pranata; Nasution, Sri Purwanti; Anggoro, Bambang Sri (Desimal: Jurnal Matematika, 2018)
This study aims to produce swed max edutainment based instructional media through metaphorical thinking approach to understanding mathematical concepts of trigonometric material. This research method used stages of Borg and Gall model development modified by Sugiyono with the aim to create a specific product and test its effectiveness. The results showed that the development of learning media has very good criteria with the average assessment of material experts of 88.8% and media by 85.7%. In the attractiveness, the test has very good criteria in small groups average percentage of 88.4% and field trials 89.6%. Learning media also affect the understanding of mathematical concepts of learners evident from the test results before and after showed improvement indicators of mathematical concepts from low to high category. The conclusion of this research is developed instructional media have very good criteria and improve understanding of the mathematical concept of learners.